Didactic experience based on mathematics competencies and soft competencies for teacher education - Quezada, Verónica Díaz; Hernández-Díaz, Alejandro; Flores del Río, George (International Journal of Evaluation and Research in Education (IJERE), 2024)
The aim of this research was to implement a didactic experience to facilitate the study of linear algebra. This article shows the potential of working the curriculum based on both disciplinary competencies and soft competencies, prioritizing collaborative learning, in future secondary school teachers of mathematics. The nature of the study is exploratory with a mixed methodology. In this article, we show the phases that constituted in its entirety the way of working during a semester in higher education and the forms of evaluation that are part of the qualitative-interpretative methodology, which include the elaboration, validation and application of a questionnaire of students' opinion on mathematical and soft skills, in addition to the analysis by categories of open answers, considering the similarities and differences found in the opinions written by the students, regarding the strengths and weaknesses of the didactic proposal, validating the usefulness of this successful teaching methodology.